Molecular marker aided breeding for blast resistant rice in Nepal - Joshi, Bal K; Bimb, Hari P; Parajuli, Gopal; Chaudhary, Bedanand (Journal of Agriculture and Environment, 2014)
Molecular markers tightly linked to target gene have been identified in different chromosomes to impose the genetic selection. This paper summarizes the progress and achievement made in breeding for blast resistance rice based on DNA markers. At least 40 genes conferring resistance to blast isolates with multiple alleles have been described. Both dominant and recessive resistance alleles have been found in many rice landraces. Highly polymorphic and easily detectable SSR markers are being used in breeding for blast resistance. Bulked segregant analysis (BSA) is the simple method for tagging resistance gene by SSR markers. Quantitative trait loci (QTLs) have also been mapped and most of them are linked to qualitative genes. Simple sequence repeat (SSR) markers linked to the gene are being used to select plants possessing the desired trait and markers throughout the genome are being used to select plants that are genetically similar to recurrent parent. Using SSR markers it may be possible to select blast resistance genotypes at any stage of crop development from any small part of crop, to conduct many round of selection, to select without inoculums, without scoring, and without testing in hot spot or artificial inoculation. Molecular based blast resistance breeding work is necessary to initiate in Nepal focusing on resistance gene tagging in Nepalese rice landraces and utilization.